SEMI-INDUSTRIAL TESTS OF A PROTOTYPE OF A NEW GRINDING EQUIPMENT – A LABYRINTH DISINTEGRATOR - Taskarina, Aizhan; Abdrakhmanov, Yermaganbet; Tussupbekova, Maral; Tyulyubayev, Renat; Deigraf, Irina; Dinara, Iskakova; Zhanar, Kassenova; Altyngul, Khaimuldinova (Journal of Applied Engineering Science, 2022)
The article provides a brief description of a prototype of a new grinding equipment – a labyrinth disintegrator, manufactured according to our developments, as well as the results of semi-industrial tests on various materials with different hardness and brittleness. A scheme for grinding the material and a dynamic scheme for moving the material through the labyrinths are presented. The results of sieve analyze of selected materials are presented, and granulometric curves for the distribution of particles of materials are constructed.